Evaluating of Microwave Drying for Hawthorn Slice as Alternative to Convective Drying - Beşir, Ayşegül; Gökmen, Süleyman; Gül, Latife Betül; Yazıcı, Fehmi; Gül, Osman (FapUNIFESP (SciELO), 2022)
Abstract This study aimed to investigate the influence of microwave drying with different power levels as alternative to convective drying method on drying kinetics and main quality attributes of hawthorn slice. At increasing microwave power values, higher drying rate and shorter drying time was observed. The page model was found to give best fit (R 2 > 0.9961, RMSE < 0.028 and χ 2 < 0.675x10-3) for all drying treatments. Although the minimum change of color and texture value were obtained at microwave power of 600 W, the convective drying caused less total color and texture change depending fresh sample. Drying process at microwave powers of 600 W and 360 W showed the best quality in terms of rehydration and bioactive properties, respectively. The findings in current work demonstrated that microwave drying at 360 W microwave power might be suitable for drying of hawthorn slices with high quality and bioactive properties as well as low operating costs.
Keywords: drying kinetics; rehydration keyword; Convective Drying; microwave drying; convective drying; Microwave Drying; hawthorn fruits; Rehydration Keyword; Hawthorn Fruits; Drying Kinetics